Enterotoxigenicity of Coagulase Positive and Negative Staphylococcus Species Isolated from Fish and Fishery Products - O.K., Sindhu; P.K., Surendran (Fishery Technology, 2025)
Seventy-five strains of coagulase positive and negative Staphylococcus species were isolated from different fish and shellfish products. These strains were investigated for enterotoxin production using Reverse Passive Latex Agglutination (RPLA) method. The different samples analysed include fresh, frozen and dried fish and shellfish, battered and breaded fish/shellfish products and fish kheema. Either one or a combination of three enterotoxins, viz., Staphylococcai Enterotoxin A, B, C (SEA, SEB, SEC) was produced by most of the strains but none were found to produce the enterotoxin SED. Out of the 75 isolates tested, 25 isolateswere coagulase positive and all these strainswere positive for thermonuclease activity. 76 % of the coagulase positive strains were toxigenic Among these, enterotoxins SEA,SEB and SEC were produced by 26.31 %, 52.63 %, and 47.36 % of the isolates respectively.None of the isolate produced SED. Multiple enterotoxin production was also observed. While 5.26 % of the strains produced SEA & SEC ,15.78 % of strains SEA & SEB and 5.26% of the strains produced SEB & SEC. None of the coagulase negative isolates produced enterotoxin.